The Implementation of Dicto-Comp (Dictation Composition) Technique in Teaching Writing Narrative Text for Eleventh Grade Students (RETAIN, 2017)
The Implementation of Dicto-Comp (Dictation Composition) Technique in Teaching Writing Narrative Text for Eleventh Grade Students Afifah English Education, Language and Art Faculty, State University Surabaya dearestafifah@gmail.com Drs. Fahri, M.A English Education, Language and Art Faculty, State University Surabaya fahri@unesa.ac.id Abstrak Menulis adalah salah satu keterampilan yang paling penting dalam belajar bahasa Inggris. Tulisan digunakan oleh para penulis untuk menerjemahkan gagasan menjadi kata-kata, sehingga bisa dikomunikasikan kepada orang lain (Flynn & Stainthorp, 2006). Namun, beberapa masalah dihadapi oleh kebanyakan siswa terkait kegiatan menulis. Kebanyakan siswa sulit mendapatkan gagasan, mengorganisir gagasan menjadi bahasa baru, mengembangkan rincian dan menyusun gagasan (Aini, 2015). Berkaitan dengan fenomena di atas, guru harus memberikan teknik yang disebut sebagai Dicto-Comp (Mendiktekan Teks) dalam pengajaran menulis. Tujuan dari penelitian ini adalah untuk mendeskripsikan penerapan teknik dicto-comp, tulisan siswa dan tanggapan/respon siswa terhadap penggunaan teknik ini. Penelitian ini menggunakan analisis kualitatif dasar. Hasil pengamatan menunjukkan bahwa penerapan teknik dicto-comp dalam pengajaran menulis sudah baik dan berjalan dengan baik. Sedangkan komposisi siswa yang dianalisis juga menunjukkan hasil yang baik. Hal itu, bisa dilihat dari jumlah siswa yang tergolong dalam kategori "Good to Average". Selain itu, hasil kuesioner menunjukkan bahwa teknik ini bermanfaat dan berguna bagi siswa dalam kegiatan menulis. Kata Kunci: Menulis, Teks Narratif, Tehnik Mendiktekan Teks Abstract Writing is one of the most important skills in learning English. Writing is used by writers to translate ideas into words, so it can be communicated to other people (Flynn & Stainthorp, 2006). However, some problem were faced by most students related to writing. As a result, most students were difficult in getting the ideas, organizing the ideas into new language, developing the details and structuring the ideas (Aini, 2015). Regarding to the phenomena above, the teacher should provide an attractive technique which called as Dicto-Comp (Dictation Composition) technique in teaching writing. The aims of this study were to describe the implementation of dicto-comp technique, the students’ composition and the students’ responses toward this technique. This research design used was basic qualitative analysis. The result of observation showed that the implementation of dicto-comp technique in teaching writing was good and run well. Meanwhile the students’ composition analyzed also showed good result. It could be seen from the numbers of students who were classified in to “Good to Average”. Moreover, the result of questionnaires showed that this technique was helpful and useful for the students in writing activity. Keywords: Writing, Narrative Text, Dicto-Comp Technique